Iodine intake and status during pregnancy and lactation before and after government initiatives to improve iodine status, in Palmerston North, New Zealand: a pilot study. Issue 4 (18th June 2013) - Brough, Louise; Jin, Ying; Shukri, Nurul Husna; Wharemate, Zirsha Roimata; Weber, Janet L.; Coad, Jane
Abstract Iodine deficiency during pregnancy and lactation may adversely affect fetal and infant development. Two initiatives were introduced in New Zealand to prevent deficiency: (1) mandatory fortification of bread with iodised salt; and (2) provision of a subsidised iodine supplement (150 μg) for all pregnant and breastfeeding women. The aim of this study was to assess iodine intake and status among a self‐selecting sample of pregnant and lactating women in Palmerston North, both before and after the two initiatives. Pregnant and breastfeeding women were recruited before (n = 25 and 32; 2009) and after (n = 34 and 36; 2011) the initiatives. Iodine concentration was determined in 24‐h urine and breast milk samples using inductively‐coupled plasma mass spectrometry. Use of supplements and salt, knowledge of iodine deficiency, and awareness of the initiatives were determined by questionnaire. Median urine iodine concentration (UIC) was higher in 2011 compared with 2009 for both pregnant (85 and 47 μg L−1) and breastfeeding (74 and 34 μg L−1) participants; median UIC were below the cut‐offs for adequate iodine status. However, in 2011, the estimated daily iodine intake during pregnancy was 217 μg day−1; 74% of women achieved the Estimated Average Requirement. Knowledge of the initiatives was low, only 28–56% were aware of the need for iodine supplements and only 15–22% were aware of the mandatory addition of iodised salt to bread. Despite initiatives, UIC of these women indicates iodine deficiency, however, dietary intakes appear adequate. Ongoing surveillance of supplement use and iodine status among pregnant and lactating women throughout New Zealand is needed to fully assess the efficacy of the initiatives. Alternative strategies may require evaluation to ensure all women have adequate iodine during pregnancy and breastfeeding.